Beautiful creatures - Garcia, Kami; Stohl, Margie 1967- (New York : Little, Brown and Co., 2009)
In a small South Carolina town, where it seems little has changed since the Civil War, sixteen-year-old Ethan is powerfully drawn to Lena, a new classmate with whom he shares a psychic connection and whose family hides a dark secret that may be revealed on her sixteenth birthday.
670L
Keywords: Supernatural; Psychic ability; Love stories; High schools; Schools; Dreams; Recluses; South Carolina; South Carolina -- History -- Civil War, 1861-1865; Young adult fiction